(untitled) (Journal of the College of Basic Education, 2022)
The pre-Islamic poet drew inspiration from the ship and the sea in his art. It is very common among poets to liken a ship to a ship, and to liken a beloved to a sea pearl. Use the terminology that denotes the use of the dexterous, meticulous, discerning gnostic, from time to time to mention The sea and its waves, the ships and their movements and shapes, and the navigators and their conditions and their work, as they used the words